Distribution of malocclusion types among thumb suckers seeking orthodontic treatment - Singh S; Utreja A; Chawla H (Wolters Kluwer Medknow Publications, 2008)
The present study was conducted to evaluate the influence of thumb sucking and its duration on the type of malocclusion. A total of 410 North Indian individuals between ages 12-30 years, 161 males and 249 females were examined. A specially designed proforma was used to record the detailed history of the individual. Among the etiological factors it was found that history of thumb sucking was present in 13.9% and significantly related to Class II div 1 malocclusion. When thumb sucking exceeded 18 months, it was found statistically significant (P < 0.1) in Class II skeletal malocclusion, in open bite (P < 0.1) and in extreme overjet (P < 0.5). Conclusion: If thumb sucking is not treated early, it can cause skeletal Class II malocclusion, anterior open bite and excessive overjet.